SIRT6 Depletion Sensitizes Human Hepatoma Cells to Chemotherapeutics by Downregulating MDR1 Expression - Xia, Yang Q.; Hua, Ren J.; Juan, Chen; Zhong, Zhou H.; Tao, Cheng S.; Fang, Ren; Lin, He; Rui, Gong; Yong, Chen (Frontiers in Pharmacology, 2018)
Multidrug resistance (MDR) due to overexpression of MDR1 is a major obstacle that hinders the treatment of hepatocellular carcinoma (HCC). In this study, we explored the function and underlying molecular mechanism of SIRT6 in multidrug resistance of HCC. Chemotherapeutic agents (doxorubicin, cisplatin and sorafenib) treatment increased SIRT6 mRNA and protein level in two HCC cell lines in a dose-dependent manner. SIRT6 depletion resulted in decreased cell viability and increased apoptosis in HCC cells treated with chemotherapeutic agents. Mechanistically, SIRT6 depletion reduced MDR1 transcription by targeting its promoter in HCC cells treated with chemotherapeutic agents. Consistently, the protein level of MDR1 was also reduced in SIRT6-depleted HCC cells. Further studies indicated that SIRT6 depletion may suppress CCAAT/enhancer binding protein β (C/EBPβ), to act as a transcriptional activator of MDR1 in HCC cells treated with chemotherapeutic agents. Importantly, forced expression of MDR1 could attenuate the apoptosis induced by chemotherapeutic agents in SIRT6-depleted cells. Taken together, these results indicated SIRT6 depletion enhanced chemosensitivity of human hepatoma cells by downregulating MDR1 expression through suppressing C/EBPβ. SIRT6 may serve as a novel target to enhance chemosensitivity in HCC cells.